Oligodendroglial deletion of ESCRT‐I component TSG101 causes spongiform encephalopathy. (23rd August 2016) - Walker, Will P.; Oehler, Abby; Edinger, Aimee L.; Wagner, Kay‐Uwe; Gunn, Teresa M.
Abstract : Research article : The E3 ubiquitin ligase MGRN1 ubiquitinates and regulates the ESCRT‐I component, TSG101. Mice lacking MGRN1 develop late‐onset spongiform neurodegeneration, characterised by widespread vacuolation of the CNS. Histologically, these vacuoles are reminiscent of the multi‐cisternal 'class E' vsp compartments that accumulate following Tsg101 knock‐down. Here, we demonstrate that deleting Tsg101 from mature oligodendrocytes in vivo also causes CNS vacuolation, but deleting Rab7 does not. This implicates defects in MVB formation that lead to the accumulation of multi‐cisternal endosomal compartments in the biogenesis of vacuoles. Consistent with this, vacuoles caused by loss of TSG101 or MGRN1 label with markers of multiple endosomal pathways. Vacuoles caused by RML prions did not label with endosomal markers, suggesting they having a different origin. Abstract : Background Information: Vacuolation of the central nervous system (CNS) is observed in patients with transmissible spongiform encephalopathy, HIV‐related encephalopathy and some inherited diseases, but the underlying cellular mechanisms remain poorly understood. Mice lacking the mahogunin ring finger‐1 (MGRN1) E3 ubiquitin ligase develop progressive, widespread spongiform degeneration of the CNS. MGRN1 ubiquitinates and regulates tumour susceptibility gene 101 (TSG101), a central component of the endosomal trafficking machinery. As loss of MGRN1 is predicted to cause partial TSG101 loss‐of‐function, we hypothesised that CNS vacuolation in Mgrn1 null mice may be caused by the accumulation of multi‐cisternal endosome‐like 'class E' vacuolar protein sorting (vps) compartments similar to those observed in Tsg101 ‐depleted cells in culture. Results: To test this hypothesis, Tsg101 was deleted from mature oligodendroglia in vivo . This resulted in severe spongiform encephalopathy, histopathologically similar to that observed in Mgrn1 null mutant mice but with a more rapid onset. Vacuoles in the brains of Tsg101 ‐deleted and Mgrn1 mutant mice labelled with endosomal markers, consistent with an endosomal origin. Vacuoles in the brains of mice inoculated with Rocky Mountain Laboratory (RML) prions did not label with these markers, indicating a different origin, consistent with previously published studies that indicate RML prions have a primary effect on neurons and cause vacuolation in an MGRN1‐independent manner. Oligodendroglial deletion of Rab7, which mediates late endosome‐to‐lysosome trafficking and autophagosome–lysosome fusion, did not cause spongiform change. Conclusions: Our data suggest that the formation of multi‐cisternal 'class E' vps endosomal structures in oligodendroglia leads to vacuolation. Significance: This work provides the first evidence that disrupting multi‐vesicular body formation in oligodendroglia can cause white matter vacuolation and demyelination. HIV is known to hijack the endosomal sorting machinery, suggesting that HIV infection of the CNS may also act through this pathway to cause encephalopathy.